Knowledge and application of first aid and treatment of snakebites among Sri Lankan North Central Province farmers - P Herath; B Banneheka; FMMT Marikar (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2024)
The application of first aid for snakebites are important in rural Sri Lanka. This study aimed to assess the current level of knowledge and application of snakebite first aid. Results revealed a substantial gap between knowledge and practices. This study highlights the need for education programs to improve snakebite management